2009
DOI: 10.4049/jimmunol.0903284
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Clock Gene Cryptochrome Regulates Arthritis via Proinflammatory Cytokine TNF-α

Abstract: The mammalian clock genes, Period and Cryptochrome (Cry), regulate circadian rhythm. We show that circadian rhythmicity and rhythmic expression of Period in the nuclei of inflammatory synovial cells and spleen cells are disturbed in mouse models of experimental arthritis. Expressions of other clock genes, Bmal1 and Dbp, are also disturbed in spleen cells by arthritis induction. Deletion of Cry1 and Cry2 results in an increase in the number of activated CD3+ CD69+ T cells and a higher production of TNF-α from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
152
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(157 citation statements)
references
References 29 publications
4
152
0
1
Order By: Relevance
“…Hashiramoto et al has also previously shown high expression of TNF-α in Cry1 −/− ;Cry2 −/− fibroblasts (35). We also observed increased phospho-IKK2 in Cry1 −/− ;Cry2 −/− fibroblasts (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…Hashiramoto et al has also previously shown high expression of TNF-α in Cry1 −/− ;Cry2 −/− fibroblasts (35). We also observed increased phospho-IKK2 in Cry1 −/− ;Cry2 −/− fibroblasts (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…We believe that our data in this paper have provided a plausible explanation: The clock disruption through CRY mutation sensitizes the transformed cells to apoptosis by inflammatory cytokines such as TNFα, which is known to be elevated in CRY mutant mice (30). Our findings also link two major signaling pathways, the circadian clock, which introduces a temporal variable into many cellular and physiological functions, and the NF-κB pathway, which is a key nodal focus in the inflammatory response at a cellular and organismal level.…”
Section: Resultsmentioning
confidence: 99%
“…In a model of collagen induced arthritis (CIA), mice lacking CRY1 and CRY2 display greater levels of TNF␣ and have heightened inflammation in their joints versus wild-type mice [146]. By ectopically expressing CRY1 in MEFs isolated from Cry1/Cry2 −/-mice, activation of a TNF␣ luciferase promoter was vastly decreased.…”
Section: The Clock Repressors: Period and Cryptochromementioning
confidence: 97%
“…[66,116] Clock 19 Global • Obese and display impaired glucose sensitivity with insulin resistance and reduced islet size [112,113] • Increased plasma triglyceride and glucose levels [85,114] • Increased fibrotic damage in model of pulmonary fibrosis [87] • Impaired anti-oxidant defense [87] Cry1/Cry2 Global • Increased NAD+ and ATP. Decreased lactate and triglycerides in MEFs [95] • Greater inflammatory damage in CIA model [146] • Increased Cxcl1. Il-6 and Tnf˛ RNA.…”
Section: Bmal1-a Master Regulatormentioning
confidence: 99%